Corrigendum to: Regional drought synchronised historical fires in dry forests of the Montane Cordillera Ecozone, Canada - Chavardès, Raphaël D.; Daniels, Lori D.; Harvey, Jill E.; Greene, Gregory A.; Marcoux, Hélène; Eskelson, Bianca N. I.; Gedalof, Ze’ev; Brookes, Wesley; Kubian, Rick; Cochrane, Jared D.; Nesbitt, John H.; Pogue, Alexandra M.; et al. (International journal of wildland fire, 2022)
Understanding climate as a driver of low- to moderate-severity fires in the Montane Cordillera Ecozone of Canada is a priority given predicted and observed increases in frequency and severity of large fires due to climate change. We characterised historical fire-climate associations using 14 crossdated fire-scar records and tree-ring proxy reconstructions of summer drought and annual precipitation from the region. We compared fire-climate associations among years when fires burned in multiple study areas. From 1746 to 1945, there were 32 years with moderate fire synchrony in which four to six study areas recorded fire. During four high fire synchrony years, 7 to 10 study areas recorded fire. Below-average annual precipitation and summer drought synchronised fires, whereas infrequent years of high fire synchrony were preceded by a wet summer. After 1945, decreased fire occurrence and synchrony reflects fire exclusion, suppression and climatic variation. Global climate change manifests as blocking high-pressure ridges that superimpose on longer fire-seasons and increased droughts. Combined, they make dry forests increasingly susceptible to synchronous fires, which are difficult to suppress as observed during the record-breaking 2017, 2018 and 2021 fire seasons in British Columbia.